2023
DOI: 10.1002/suco.202201245
|View full text |Cite
|
Sign up to set email alerts
|

Sustainability assessment of recycled aggregate concrete structures: A critical view on the current state‐of‐knowledge and practice

Abstract: The environmental impacts of activities such as raw material extraction, construction of infrastructure, and demolition, place construction as one of the sectors that exert the highest pressures on the environment, society, and economy. Some of the major environmental impacts for which the construction industry is responsible are mineral resource depletion, greenhouse gas emissions, and waste generation. Among the different strategies that exist to decrease such impacts, recycling demolition waste into recycle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 86 publications
0
5
0
1
Order By: Relevance
“…The environmental impacts associated with the recycled materials have been evaluated using a cut-off allocation method. However, alternative approaches should be evaluated similarly to studies already conducted for recycled concrete by Marinkovi et al [ 48 ]. For example, by comparing results from cut-off to those of economic allocation, the benefits of increasing or reducing plastic recycling on a larger scale can be better evaluated and provide a broader context.…”
Section: Research Outlookmentioning
confidence: 99%
“…The environmental impacts associated with the recycled materials have been evaluated using a cut-off allocation method. However, alternative approaches should be evaluated similarly to studies already conducted for recycled concrete by Marinkovi et al [ 48 ]. For example, by comparing results from cut-off to those of economic allocation, the benefits of increasing or reducing plastic recycling on a larger scale can be better evaluated and provide a broader context.…”
Section: Research Outlookmentioning
confidence: 99%
“…Das Ergebnis wird durch die getroffenen Annahmen bei der Erstellung der Ökobilanz erheblich beeinflusst. So haben die Wahl der Ansatzstrategie und der Systemgrenzen sowie die Qualität und Verfügbarkeit der Daten einen signifikanten Einfluss auf das Ergebnis [8][9][10][11].…”
Section: Introductionunclassified
“…53 LCA has been used extensively to determine the environmental performance of concrete. [54][55][56] Previously, an impact assessment of geopolymer concrete containing different combinations of industrial wastes showed a considerable decrease in greenhouse gas emissions as compared to ordinary concrete. 57 Due to extensive inconsistency in the specifications of waste products, there is a need to study the impact of using different source materials like AGWA's in geopolymer concrete using the LCA methodology.…”
Section: Introductionmentioning
confidence: 99%
“…Life cycle assessment (LCA) has evolved as a systematic method to ascertain the environmental impact of a product during its lifetime 53 . LCA has been used extensively to determine the environmental performance of concrete 54–56 . Previously, an impact assessment of geopolymer concrete containing different combinations of industrial wastes showed a considerable decrease in greenhouse gas emissions as compared to ordinary concrete 57 .…”
Section: Introductionmentioning
confidence: 99%